Mother Ira's Communication Style In Thesis Educational Content On @buiramira's Tiktok Account - Abdul Aziz; Ferrari Lancia; Liliyana Liliyana; Risma Robiah Alawiyah (PT ARRUS Intelektual Indonesia, 2023)
Communication style refers to a person's ability to regulate their behavior in sending and receiving messages. Every individual has their way of communicating. A person is unique, and unique is what differentiates him from others because the more interesting the communication style used, the easier the person is to be recognized. This research, which uses the concept of Aristotle's Rhetoric, aims to determine Mrs. Ira's communication style in the thesis educational content on the TikTok account @buiramira. The qualitative descriptive content analysis method was used in this research by carrying out data collection techniques using observation, documentation, and interviews. The research results show that the rhetorical style used by Ira Mira in her educational content is less formal and could be more the Ethos aspect; it can be seen through extensive knowledge and honesty so that the message conveyed can be trusted. The Phatos aspect can be seen through a voice style that makes a lot of nonverbal affirmations. Meanwhile, the Logos aspect can be seen through Ira's mother tongue, which is concise, clear, and easy to understand. Mrs. Ira uses more imaginary expressions and hand movements to emphasize the message in the Logos aspect